Emodin Protects Against Acute Pancreatitis-Associated Lung Injury by Inhibiting NLPR3 Inflammasome Activation via Nrf2/HO-1 Signaling - Gao Z; Sui J; Fan R; Qu W; Dong X; Sun D (Dove Medical Press, 2020)
Zhenming Gao,1,* Jidong Sui,1,* Rong Fan,2 Weikun Qu,1 Xuepeng Dong,1 Deguang Sun1 1Department of Hepatopancreatobiliary Surgery, The Second Affiliated Hospital of Dalian Medical University, Dalian, Liaoning 116027, People’s Republic of China; 2Department of International Medicine, The Second Affiliated Hospital of Dalian Medical University, Dalian, Liaoning 116027, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhenming Gao; Rong FanDepartment of Hepatopancreatobiliary Surgery, The Second Affiliated Hospital of Dalian Medical University Department of International Medicine, The Second Affiliated Hospital of Dalian Medical University, 467 Zhongshan Road, Dalian, Liaoning 116027, People’s Republic of ChinaEmail gaozhenmingdl@163.com; fanrongdl@126.comAim: Lung injury is a common complication of acute pancreatitis (AP), which leads to the development of acute respiratory distress syndrome and causes high mortality. In the present study, we investigated the therapeutic effect of emodin on AP-induced lung injury and explored the molecular mechanisms involved.Materials and Methods: Thirty male Sprague-Dawley rats were randomly divided into AP (n=24) and normal (n=6) groups. Rats in the AP group received a retrograde injection of 5% sodium taurocholate into the biliary-pancreatic duct and then randomly assigned to untreated, emodin, combined emodin and ML385, and dexamethasone (DEX) groups. Pancreatic and pulmonary injury was assessed using H&E staining. In in vitro study, rat alveolar epithelial cell line L2 cells were exposed to lipopolysaccharide and treated with emodin. Nrf2 siRNA pool was applied for the knockdown of Nrf2. The contents of the pro-inflammatory cytokines in the bronchoalveolar lavage fluid and lung were determined using enzyme-linked immunosorbent assay. The expressions of related mRNAs and proteins in the lung or L2 cells were detected using real-time polymerase chain reaction, Western blot, immunohistochemistry and immunofluorescence.Key Findings: Emodin administration alleviated pancreatic and pulmonary injury of rats with AP. Emodin administration suppressed the production of proinflammatory cytokines, downregulated NLRP3, ASC and caspase-1 expressions and inhibited NF-κB nuclear accumulation in the lung. In addition, Emodin increased Nrf2 nuclear translocation and upregulated HO-1 expression. Moreover, the anti-inflammatory effect of emodin was blocked by Nrf2 inhibitor ML385.Conclusion: Emodin effectively protects rats against AP-associated lung injury by inhibiting NLRP3 inflammasome activation via Nrf2/HO-1 signaling.Keywords: emodin, acute pancreatitis, lung injury, Nrf2, NLRP3 inflammasome